Detection of an emerging novel sublineage Ind2001BD1 and lineage PanAsia of foot-and-mouth disease virus serotype O in cattle in Manikgonj district of Bangladesh, 2018 - Ali, Md Zulfekar (Open Vet J, 2020)
BACKGROUND: Foot-and-mouth disease (FMD) is an endemic disease of cloven-hoofed animals in Bangladesh and multiple outbreaks occur every year because of the FMD virus (FMDV). AIM: The aim of the present investigation was to determine the molecular characterization of the VP1 coding region of FMDV serotype O outbreak in cattle. METHODS: A total of four tongue epithelial specimens were collected from clinically FMD-positive cattle during June 2018 in Manikgonj district of Bangladesh. RESULTS: All four isolates were recorded positive for FMDV serotype O. The phylogenetic analysis showed that two isolates were clustered within an emerging novel sublineage Ind2001BD1 under lineage Ind2001 of FMDV serotype O, which was identified during 2012–2016 in Bangladesh. One isolate was clustered within the lineage PanAsia of FMDV serotype O and was closely related to an isolate identified in Nepal in 2009. The phylogenetic reconstruction revealed that all the four isolates belong to the Middle East–South Asia topotype. CONCLUSION: Therefore, multiple lineages of the FMDV serotype O are circulating among the cattle in the outbreak area, which make it more complex for the FMD control program in Bangladesh. A comprehensive study on the genetic characteristics of FMDV across the country is required for effective FMD prevention and control strategy.